Acting on the potentially reversible causes of traumatic cardiac arrest: Possible but not sufficient. (August 2021) - Savary, Dominique; Douillet, Delphine; Morin, François; Drouet, Adrien; Moumned, Thomas; Metton, Pierre; Carneiro, Bruno; Fadel, Marc; Descatha, Alexis
Abstract: Introduction: Traumatic cardiac arrest (TCA) guidelines emphasize specific actions that aim to treat the potential reversible causes of the arrest. The aim of this study was to measure the impact of these recommendations on specific rescue measures carried out in the field, and their influence on short-term outcomes in the resuscitation of TCA patients. Methods: We conducted a retrospective study of all TCA patients treated in two emergency medical units, which are part of the Northern Alps Emergency Network, from January 2004 to December 2017. We categorised cases into three periods: pre-guidelines (from January 2004 to December 2007), during guidelines (from January 2008 to December 2011), and post-guidelines (from January 2012 to December 2017). Local guidelines, a physician education programme, and specific training were set up during the post-guidelines period to increase adherence to recommendations. Utstein variables, and specific rescue measures were collected: advanced airway management, fluid administration, pelvic stabilisation or tourniquet application, bilateral thoracostomy, and thoracotomy procedures. The primary endpoint was survival rate at day 30 with good neurological status (cerebral performance category scores 1 & 2) in each period, considering the pre-guidelines period as the reference. Results: There were 287 resuscitation attempts in the TCA cases included, and 279 specific interventions were identified with a significant increase in the number of fluid expansions (+16%), bilateral thoracostomies (+75%), and pelvic stabilisations (+25%) from the pre- to post-guidelines periods. However, no improvement in survival over time was found. Conclusion: Reversible measures were applied but to a varying degree, and may not adequately capture pre-hospital performance on overall TCA survival.